The Role of the East Asian-Australasian Flyway Partnership (EAAFP) in the Conservation of Sembilang National Park 2017-2022 - Silvia Nurhaliza Faridah; Wildan Ilmanuarif Shafar; Andini Maulidanisa; Ken Arok Satria Dewangga; Mutiara Mutiara; Salfa Desthiar (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study examines the role of the East Asian–Australasian Flylĺway Partnership (EAAFP) in the conservation efforts of Sembilang National Park during the 2017–2022 period. Sembilang National Park is a vital wetland area for migratory birds along the East Asian–Australasian Flyway. This research employs a qualitative-descriptive approach using literature review and document analysis, and is grounded in the theory of compliance with international regimes by Chayes and Chayes. The findings reveal that EAAFP contributes through institutional capacity building, conservation project funding, local community involvement, and international environmental diplomacy. Although the partnership lacks binding legal authority, EAAFP promotes voluntary compliance through reputational incentives and technical support. Tangible impacts can be seen in the implementation of bird monitoring programs, species identification training, and the development of community-based ecotourism. However, challenges such as limited resources, lack of local policy integration, and sustainability after external support remain significant. This study emphasizes that successful transboundary conservation relies on multilevel collaboration and the strengthening of local institutions